The effects of weather variability on patterns of genetic diversity in Tasmanian bettongs. Issue 8 (15th March 2021) - Proft, Kirstin M.; Bateman, Brooke L.; Johnson, Christopher N.; Jones, Menna E.; Pauza, Matthew; Burridge, Christopher P.
Abstract: While the effects of climate (long‐term, prevailing weather) on species abundance, range and genetic diversity have been widely studied, short‐term, localized variations in atmospheric conditions (i.e., weather) can also rapidly alter species' geographical ranges and population sizes, but little is known about how they affect genetic diversity. We investigated the relationship between weather and range‐wide genetic diversity in a marsupial, Bettongia gaimardi, using dynamic species distribution models (SDMs). Genetic diversity was lower in parts of the range where the weather‐based SDM predicted high variability in probability of B. gaimardi occurrence during 1950–2009. This is probably an effect of lower population sizes and extinction–recolonization cycles in places with highly variable weather. Spatial variation in genetic diversity was also better predicted by mean probabilities of B. gaimardi occurrence from weather‐ than climate‐based SDMs. Our results illustrate the importance of weather in driving population dynamics and species distributions on decadal timescales and thereby in affecting genetic diversity. Modelling the links between changing weather patterns, species distributions and genetic diversity will allow researchers to better forecast biological impacts of climate change.